Analisis Presepsi Penumpang Angkutan Umum Kota (Pete-Pete) Trayek Makassar Mall-Perumas Antang - Makupiola, Christy Agata; Azis, Risky Aprianti (Indo Green Journal, 2024)
Universal transport is one of the prominent factors in people's lives, including the people in Makassar City as a means of supporting their daily movement activities. Arranging suitable transport is a prominent thing that the government and the public must consider as transportation service providers to meet community needs. The purpose of this study is to find out the perceptions among ordinary passengers in the city transportation (pete-pete) route Makassar Mall - Perumnas Antang. This type of research is descriptive research that: c Service oncoming approach based on five dimensions name dependability, responsiveness, confidence, empathy, and then physical evidence. Data from the survey results were analyzed descriptively using frequencies and graphs to analyze the characteristics and then perceptions of city public transport passengers (pete-pete) on route H. The results proved it overall the defendants were satisfied with the public transportation services provided.